PENGGUNAAN METODE FUZZY MAMDANI UNTUK RANCANG BANGUN SISTEM PEMILIHAN PROGRAM STUDI PADA KAMPUS AMIK-BSI JAKARTA - Ratna Setyaningsih (LPPM Nusa Mandiri, 2017)
AMIK BSI Jakarta is the largest vocational education in Indonesia. Currently, AMIK BSI Jakarta has three (3) courses: Computerized Accounting, Information Management, and Computer Engineering. AMIK BSI has 15.133 active students. Of the many students have a background in different schools. After graduating from high school, the students wanted to go to college to continue their education even higher, but after entering college students are experiencing difficulties because it was not able to follow the lessons and find one of the majors, as a result of these students through college with no spirit and not serious. We need logic to solve the problem, and the need to support a decision in the selection process the selection of majors and giving recommendations courses according to the parameter by using fuzzy logic Mamdani method to determine the relationship of the determination of academic study programs. Reasons for using fuzzy logic Mamdani method for decision support.